MENENTUKAN SUHU OPERASI MESIN DRYER DENGAN METODE TAGUCHI UNTUK MENGURANGI JUMLAH BENANG BASAH PADA DIVISI YARN DYING DI PT MULIA KNITTING FACTORY - Ginting, Meriastuti; Wijaya, Felix Surya (Teknik dan Ilmu Komputer, 2013)
PT Mulia Knitting Factory (PT KMF) is a textile industry that produces cloth rolls for the manufacture of clothing in addition to Â underwear as its main product. There are two kinds of cloth rolls produced: plain cloth rolls and patterned cloth rolls. After the drying process, wet cloth rolls were still found. The operatorâs lack of training, the old drying machine, the different absorption level of materials, and the inappropriate temperature were estimated to be the causes. PT MKF wanted to decrease the wet cloth rolls after the drying process by improving the machine performance so that potential losses can be minimized. The Taguchi method is therefore appliedto determine the process temperature to be used in the drying process. Taguchi method resulted in100oC internal temperature and 96oC external temperature for white yarn,103oC internal temperature and 98oC external temperature for light colored yarn, and 108oC internal temperature and 103oC external temperature for dark colored yarn. Using the obtained temperature settings had decreased the numbers of wet yarns. The white yarn decreased from 20.2 chees to 10.999 chees,Â the light colored yarn decreased from 12 chees to 6.999 chees, and the dark colored yarn from 25chees to 10.833 chees.Â Keywords: improvement, Taguchi Method, process temperature, desain of experiment